2022
DOI: 10.3389/fmicb.2022.934031
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Commercially Available Nanoparticles on Soil Bacterial Community and “Botrytis fabae” Caused Brown Spot: In vitro and in vivo Experiment

Abstract: This study revealed the possible effects of various levels of silver nanoparticle (AgNP) application on plant diseases and soil microbial diversity. It investigated the comparison between the application of AgNPs and two commercial nanoproducts (Zn and FeNPs) on the rhizobacterial population and Botrytis fabae. Two experiments were conducted. The first studied the influence of 13 AgNP concentration on soil bacterial diversity besides two other commercial nanoparticles, ZnNPs (2,000 ppm) and FeNPs (2,500 ppm), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This work is licensed under the Creative Commons Attribution 4.0 International License study advised he use of AgNPs as an antibacterial agent in the agricultural sector. 32 As shown in Tables 7 and 8, our results revealed that the tested treatments were more effective at reducing or inhibiting aflatoxin production than reducing A. flavus growth. Our findings are consistent with those of , 85 who reported that the inhibitory effect on fungal growth was not directly related to mycotoxin inhibition.…”
Section: Fungal Experimentsmentioning
confidence: 52%
See 1 more Smart Citation
“…This work is licensed under the Creative Commons Attribution 4.0 International License study advised he use of AgNPs as an antibacterial agent in the agricultural sector. 32 As shown in Tables 7 and 8, our results revealed that the tested treatments were more effective at reducing or inhibiting aflatoxin production than reducing A. flavus growth. Our findings are consistent with those of , 85 who reported that the inhibitory effect on fungal growth was not directly related to mycotoxin inhibition.…”
Section: Fungal Experimentsmentioning
confidence: 52%
“…31 The antibacterial properties of silver have been known for more than 100 years, and it is used in treatments. 32 Copper nanoparticles (CuNPs) can interact with the organelles of microorganisms and with thiol groups in enzymes and proteins, 29,33 which leads to the accumulation of copper in vacuoles and cell walls as granules and inhibits microorganism growth. 34 CuNPs have greater bactericidal activity due to their larger surface area, which results in synergistic effects that exert antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to a new era of using nanoparticles to enhance agricultural production, but their potential harmful effects on the environment and vegetation should not be ignored (Iqbal et al, 2020;Abdelghany et al, 2022). Silver nanoparticles (AgNPs) have a lot of potential in agriculture, especially when it comes to increasing the pace and development of diploid and triploid seeds (Khafaga et al, 2022;Sabra et al, 2022;Abdelsalam et al, 2022a). Capping phytochemicals in green nanoparticle manufacturing has a positive impact on agriculture.…”
Section: Introductionmentioning
confidence: 99%